Advanced methodologies and technologies in business operations and management - Khosrow-Pour, Mehdi, 1951- (Business Science Reference, 2019)
"This book provides emerging research on business tools such as employee engagement, payout policies, and financial investing to promote operational success. While highlighting the challenges facing modern organizations, readers will learn how corporate social responsibility and utilizing artificial intelligence improve a company's culture and management"--